Utilization of Google My Business as a Tourism Promotion Media Using Local Search Engine Optimization - Purbasari, Ayi; Maryono, Ghesti Prabawati; Mulyanto, Ferry; Gusdya, Wanda (Pandawan Sejahtera Indonesia, 2021)
The tourism industry is an industry that continues to grow in the world, including in Indonesia. Likewise, Kebumen Regency has various tourism potentials ranging from water tourism, mountain tourism, culinary tours, cave tours, cultural tourism and others. One of them is Curug Sindaro, which is located in the north of Kebumen Regency which is precisely located in Wadasmalang Village, Karangsambung District, Kebumen Regency, Central Java. However, in the process of developing and managing it, the tour, which was inaugurated on March 3, 2019, is increasingly experiencing a decline in visitors. Which is where, the main problem is that the promotion is still not optimal. In the existing tourism development process, of course, requires the media used to carry out promotions with a good marketing strategy. In order to be easily affordable, the right marketing strategy to use is an online marketing strategy. By analyzing promotional needs and analyzing keywords, it can maximize promotion. The purpose of this research is to implement Local SEO using Google My Business as a promotional medium for Wisata Curug Sindaro which is an online marketing strategy. If the Sindaro waterfall tour is promoted through Google my business, tourists around the Sindaro waterfall will find it easy to find Sindaro waterfall tourism through google and it is hoped that visitors will increase. Because, in this Google My Business has sufficient features for promotion. With the initial stage of registering a Google My Business account, then claiming an existing business. Because previously the Sindaro Curug Tour was already on Google Pages. With several stages of verification and changing the cellphone number that stated the Google My Business account for Sindaro Curug Tourism has been successfully created. However, due to the verification method there are obstacles that have been successfully created is the web page for the Sindaro Waterfall Tour.